Does Reward Enforcement and Organization Boundaries lead to Sustainable Supply Chain Performance in Indonesian SMEs? A Moderating role of Work Discretion - Nandang Najmulmunir (International Journal of Supply Chain Management, 2020)
Manufacturing small and medium sized enterprises (SMEs) of Indonesia are suffering with low business performance due to ineffective supply chain activities. Therefore, this study is an attempt to highlight the issue of low supply chain performance in manufacturing SMEs of Indonesia and one of the attempts to provide the solution of this issue. The current study examined the effect of three corporate entrepreneurship dimensions on supply chain. Dimensions include; reward enforcement, organization boundaries and work discretion. Therefore, objective of this study is to investigate the effect of reward enforcement, organization boundaries and work discretion on sustainable supply chain performance among Indonesian manufacturing SMEs. Data were collected from the manufacturing SMEs of Indonesia and employees of these SMEs were considered as the respondents of the study. Finally, data were analysed through statistical software. Results of the study revealed that corporate entrepreneurship is important to handle supply chain issues. It is found that reward enforcement and organization boundaries have the key contribution to provide sustainable supply chain performance. Moreover, work discretion also has crucial role to enhance the positive effect of corporate entrepreneurship on sustainable supply chain performance.